Taṭbīq Tarīqat Ḥifẓ al-Naẓam fī Taʿlīm al-Qawāʿid wa-Atharuhū fī Muyūl al-Tullāb wa-Qudratihim ʿalá Fahm al-Qawāʿid al-ʿArabīyah - Jamilatussa'diyah Jamilatussa'diyah; Siti Sanah; Ilyas Rifa'i (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
The learning method is considered as one of the most important components in the learning process. A teacher should be able to choose and use learning methods that are in accordance with learning objectives and needs of students because it can increase interest and learning outcames. This study aims to determine the effect of applying the nazam memorization method in qawa’id learning on students` interest in learning and the ability to undestand Arabic rules at the Al Hikmah Islamic Boarding School Tasikmalaya. This research is a quantitative reseach with correlational descreptive method. The result showed that the application of the nazam memorization method in qawa’id learning reached an average of 83,16% (very good category), students` interest in learning qawa’id reached an average of 74,8% (good category), the ability to understand the rules of Arabic reached an average of 75,9% (good category), the effect of applying the nazam memorization method in qawa’id learning on students` interest reached 35% meaning that there are other factors of 65% that can affect students` interest in learning, and the effect of applying the nazam memorization method in qawa’id learning on the ability to understand qawa’id reached 36% meaning that there are other factors of 64% that can affect the ability to understand qawa’id.